Validity of Digital Signature as Evidence in Electronic Commerce - Ruslijanto, Patricia Audrey (UI Scholars Hub, 2021)
Trade is a way to promote economy, recognized that trade is important, urge the emergence of new trading concept. Electronic Commerce is the succumbed attendance of faceless trading. Alongside the development of technology, crimes also develop rapidly. Cyber crime is the type of crime in the virtual world. Recognized this problem, the appearance of security system in cryptography is well developed. Digital Signature is the manifestation of cryptography in asymmetric cryptosystem. Ironically well problem solving of this condition is not entails with its position as evidence in electronic contract. In evidence law, the presence of digital signature is approved as evidence in electronic commerce. It based on the equality of hash function. The validity of digital signature also approved as evidence in electronic commerce based on the approval of art. 11 Law No 11/2008 on Information and Electronic Transaction, which emphasize the legal position of digital signature as valid evidence in electronic commerce. Considering the constraints that arise in digital signature verification divided into Non juridical consist of technology and cultural obstacle. In case a dispute occurs either in transnational area, the jurisdiction that used in cyberspace area need precise principles rooted from the principle of international law. These principles are: subjective, objective territoriality, passive nationality, protective principle and universality interest jurisdiction, theory of the law of the server and theory of international space.